Estudio de factibilidad para la creación de un departamento de asesoría en gestión financiera para la Asociación de Productores de ciclo corto “Aprocico”, cantón Quevedo año 2014 - Gáleas Morán, Gianela Vanessa (2015)
This project aims to conduct a feasibility study for the creation of a department of financial management advice for Producers Association APROCICO short cycle. This project is aimed at developing a financial management, seeking alternative financial development on behalf of the Association, the investigated object will not only ensure the development of financial management , presenting alternative financial development for the Association but in the environment increasing sectoral working places and contributing to the improvement in the economy of the population and investors , as well as the growth of the extent planting short-cycle products nationally and good quality . The implementation of this project is to provide an avenue for expanding agricultural activity of short-cycle rice , corn and soybeans in the province of Los Rios and surrounding areas , as well as the expansion of production favors the creation of new jobs and qualified product contributing to the generation of value added in the agricultural line . By conducting market research through surveys , 92% would agree that the counseling department believes in financial management APROCICO . The financial study was obtained that the project is feasible because the NPV is positive $ 32,585.66 ; IRR is 25 % and the B / C ratio generate a gain of 0.91 cents for every dollar spent.